KUALITAS SISTEM DAN KUALITAS INFORMASI PEMASARAN TERHADAP KINERJA KARYAWAN DI PT. INTI - Ardi Hidayat; Muhammad Saleh (Program Pascasarjana UIN Sultan Maulana Hasanuddin Banten, Jalan Jenderal Sudirman No. 30, Serang - Banten 42118, 2017)
This study aims to determine the effect of the quality system used and the quality of information generated on the performance of employees in PT. INTI Ltd. Bandung. In addition, this study aims to test the main hypothesis that the quality system and quality of information affects the performance employees at PT. INTI Ltd. Bandung. Analysis technique using the formulas in the calculation of product moment correlation of the data collected through the questionnaires filled out by employees at PT. INTI Ltd. Bandung system using SIPP. Based on the analysis by using the formula the product moment correlation test of the hypothesis is proven that the quality system and quality of information affect the performance of employees in PT. INTI Ltd. Bandung by 55.9%. In fact the system does not affect the quality of employee performance, and quality of information affects the performance of employees, it is proved by calculation of 6.607 tcount greater than ttable of 1.6794 with a variable rate  = 5% and dk = n-2 with one-sided test. In addition to the conceptual elements or indicators of the quality system include ease to use, response time, system reliability, flexibility and security system is perceived by most respondents is moderate. In the variable quality of information with an indicator of completeness, relevant, accurate, and timely assessments are at medium. Including variables in the employee's performance PT. INTI Ltd. Bandung, perceived by most respondents is currently with the indicators of productivity and efficiency. Keywords: quality systems, quality of information, employee performance